2015
DOI: 10.1016/j.cmi.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of the multidrug-resistant extended-spectrum β-lactamase-producing Escherichia coli O25b-ST131 clone and the role of house crow (Corvus splendens) foraging on hospital waste in Bangladesh

Abstract: Two hundred and thirty-eight faecal samples from crows foraging on hospital wastes were analysed for extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae. ESBL-producing crow isolates were characterized and compared with 31 patient isolates. Among the crows, 59% carried ESBL producers. These included Escherichia coli, Klebsiella pneumoniae, Raoultella terrigena and Enterobacter cloacae harbouring the genes for CTX-M-1, CTX-M-15, CTX-M-55, CTX-M-79, and CTX-M-14. Human isolates carried only the CTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…Several publications have reported the frequent occurrence of ESBL-producing ST131 and ST648 strains in wild-bird populations and poultry, possibly pointing toward an increased colonization ability of ESBL E. coli in the avian gut (23)(24)(25). To test whether ST131 and ST648 would differ in this respect in vivo, we performed colonization experiments for ST648 and ST131 in chicken intestines.…”
Section: Resultsmentioning
confidence: 99%
“…Several publications have reported the frequent occurrence of ESBL-producing ST131 and ST648 strains in wild-bird populations and poultry, possibly pointing toward an increased colonization ability of ESBL E. coli in the avian gut (23)(24)(25). To test whether ST131 and ST648 would differ in this respect in vivo, we performed colonization experiments for ST648 and ST131 in chicken intestines.…”
Section: Resultsmentioning
confidence: 99%
“…Although the numbers are too small to draw any definite conclusion, it is interesting to note that the prevalence in Cattle Egrets sampled at the dump in Leon (33%, Table 4) was much higher than the average in the cohort of wild birds in our study (8%), suggesting that proximity to human activities might contribute to colonization of birds with antibiotic-resistant bacteria. 11,26,27 The bla CTX-M is a major ESBL type that has high clinical importance. Different types of clinically relevant bla CTX-M genotypes have been reported in humans as well as in different reservoirs, including wild birds and poultry, in many parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…This study indicates the absence of VRE harboring vanA and vanB genes among crows foraging on hospital wastes even though they were potential carriers of ESBL-producing Enterobacteriaceae ( 28 ). Thus, spread through hospital waste via house crows does not seem to be a major mechanism for dissemination of VRE in Bangladesh.…”
Section: Results Discussion and Conclusionmentioning
confidence: 85%
“…A study on these samples demonstrated that 59% of the crows living on hospital waste were potential carriers of clinically relevant ESBL-producing E. coli and Klebsiella ( 19 ), and hospital waste has been reported as a potential source of antibiotic-resistant bacteria ( 19 , 27 ). These crows were reported as potential carriers of clinical relevant human-associated ESBL-producing E. coli ST13-O25b clones, likely because of their foraging behaviors in hospital waste dumps ( 28 ). It has also been documented that wild birds can carry VRE and ESBL-producing bacteria simultaneously ( 16 ).…”
Section: Results Discussion and Conclusionmentioning
confidence: 99%